PENDIDIKAN BERKARAKTER PERSPEKTIF DALAM PEMBANGUNAN DAN PEMBENTUKAN MORAL PESERTA DIDIK - Luh Kompiang Sari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The challenges of globalization that are so complex and unpredictable require this nation to find an appropriate and comprehensive formula, so that it can be a savior of national identity. The formula should be able to strengthen the symbols of the personality of the Indonesian people in a structured and Indonesian way in the midst of the influence of global science and technology. Social problems in the community with great concern, with the declining moral and ethical stage of politics and economics, the role of formal education is an important process for the formation of nation and character building. Good character consists of knowledge about virtue, the desire to do good and do good, or positive thinking habits, habits of feeling in the heart, and habitual behavior. Education about the value (character) of students needs to be effective because of the various negative influences that can influence behavior such as, deviant behavior tendencies of students. Character Development and Education relates to: moral knowledge, moral feelings and moral behavior. From these three components determine moral life. For this reason it needs to be studied carefully in efforts to build a new Indonesia that is often referred to as civil society.Keywords: Character Education, Development and Formation of Morals, Students